What to do in case of an endoscopic image of gastric necrosis or ischaemia post-funduplication? A case report - Peña, Ricardo-Raziel; H. Gallo, Ricardo; Tristán-Tenorio, Carlo A.; J. Ruelas, Saúl E.; Ramírez-Miguel, Williams O.; Higuera-Hidalgo, Francisco; Etchegaray-Dondé, Agustín (International Journal of Research in Medical Sciences, 2023)
The association of gastric ischemia with a fundoplication is very rare and its management is not always surgical. The present paper describes the mechanism of post-fundoplication gastric ischemia that occurred in a patient diagnosed with gastroesophageal reflux disease treated with a Nissen-type gastric fundoplication. A clinical case of the Foregut Clinic of the Hospital General de Mexico (HGM) is presented. This is a 24-year-old patient undergoing a Nissen-type fundoplication who was discharged without eventualities and who presented intestinal occlusion, acute gastric dilation and gastric ischemia.